Heavy metals and TPH effects on microbial abundance and diversity in two estuarine areas of the southern-central coast of São Paulo State, Brazil - Pinto, Aline Bartelochi [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Amaro Pinheiro, Marcelo Antonio [UNESP]; Carelli Fontes, Roberto Fioravanti [UNESP]; Fernandes Cardoso de Oliveira, Ana Julia [UNESP] (Elsevier B.V., 2015)
Coastal areas may be impacted by human and industrial activities, including contamination by wastewater, heavy metals and hydrocarbons. This study aimed to evaluate the impact of hydrocarbons (TPH) and metals on the microbiota composition and abundance in two estuarine systems in the coast of Sao Paulo: the Santos (SE) and Itanhaern (IE) estuaries. The SE was found to be chronically contaminated by heavy metals and highly contaminated by hydrocarbons. This finding was correlated with the increased density of cyanobacteria in sediments and suggests the possible use of cyanobacteria for bioremediation. These contaminants influence the density and composition of estuarine microbiota that respond to stress caused by human activity. The results are troubling because quantitative and qualitative changes in the microbiota of estuarine sediments may alter microbiological processes such as decomposition of organic matter. Moreover, this pollution can result in damage to the environment, biota and human health. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Estuaries; Heavy metals; Hydrocarbons; Cyanobacteria; Heterotrophic bacteria; Fungi